Experimental analysis on the rapid measurement of a high precision Brillouin scattering spectrum in water using a Fabry–Pérot etalon. (24th March 2016) - Zhou, Bo; Fan, Qiming; Ma, Yong; Yao, Yuan; Li, Hao; Huang, Jun; Liang, Kun
Abstract: The Brillouin lidar system with a Fabry–Pérot (F–P) etalon has been widely used in remote sensing to study ocean characteristics such as temperature, sound speed, etc. In this system, the measurement error stemming from the spectral broadening of an F–P etalon was typically neglected in applications where high measurement accuracy was not essential. In this paper, an integration method on radius and a convolution method on frequency are proposed to remove the broadening effect and improve the measurement accuracy, respectively. Experiments of underwater Brillouin scattering show that both fitting methods effectively reduce the measurement error due to the transmission function of an F–P etalon. A temperature accuracy of 0.1 °C and a salinity accuracy of 0.5‰ were achieved. Moreover, with the convolution method, the computational cost was reduced to 3 s, which enables rapid measurement of Brillouin shift and linewidth and makes the on-line remote sensing applications possible.